Technology as a Response to the Challenges of Aging Society and Shrinking Labor Markets - Bazela, Maciej (My University, 2022)
This paper examines how Japan has embraced advanced technologies to address the challenges of an aging society and shrinking labor markets. Using Japan as a case study, this paper explores the relationship between human dignity, the intrinsic value of work, and the fourth industrial revolution. The paper is divided into four sections. The first section describes the scale of aging and shrinking labor markets in Japan, and the measures that the Japanese government has used to tackle these problems. The second section offers a selection of five mini cases that show how advanced technologies are used in different sectors of the Japanese economy. The third section outlines some ethical concerns that go beyond utilitarian benefits of using advanced technologies to address the problem of aging. The perspective of Catholic Social Teaching (CST) is adopted as a main advocate of a person-centered social ethics. The fourth section offers an assessment of Japan’s experiment and outlines further research opportunities.